STRATEGI PENDAMPINGAN BELAJAR MEMBACA DI MI NURURRAHMAH: Perkembangan Kemampuan Membaca Siswa, Efektivitas Strategi Berdasarkan Gaya Belajar , Respons dan Peran Guru Pendamping , Kendala dan Solusi dalam Pelaksanaan Kegiatan - Zilfania Qathrun Nada; Yuliatin Dwi Wardani; Rika Lailatul Hasanah3, Fina Rahmatika4, Selvia Wulandari5 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the reading skills of first and second-grade students at MI Nururrahmah who experience reading difficulties through a learning assistance strategy based on learning styles. The research method used was a descriptive approach through a Community Service Program (PKM) conducted from March 15 to April 26, 2025, involving six students with reading difficulties. The instruments used included observation, interviews, and informal evaluations during the activities. The results showed that the application of learning methods tailored to students' learning styles (auditory, visual, and kinesthetic) significantly increased students' motivation and reading skills. Auditory learners improved through the Listen and Repeat and Singing Methods, visual learners benefited from the use of Flashcards, and kinesthetic learners showed progress through the air-writing method. This program also strengthened teachers' capacity to understand students' learning styles and implement adaptive teaching strategies within the school environment.